Developmental evaluation during the COVID-19 pandemic: Practice-based learnings from projects in British Columbia, Canada. (March 2023) - Iyamu, Ihoghosa; Berger, Mai; Fernando, Saranee; Snow, M Elizabeth; Salmon, Amy
In this article, we explore experiences and learnings from adapting to challenges encountered in implementing three Developmental Evaluations (DE) in British Columbia, Canada within the evolving context of the COVID-19 pandemic. We situate our DE projects within our approach to the DE life cycle and describe challenges encountered and required adaptations in each phase of the life cycle. Regarding foundational aspects of DEs, we experienced challenges with relationship building, assessing and responding to the context, and ensuring continuous learning. These challenges were related to suboptimal embeddedness of the evaluators within the evaluated projects. We adapted by leveraging online channels to maintain communications and securing stakeholder engagement by assuming non-traditional DE roles based on our knowledge of the context to support project goals. Additional challenges experienced with mapping the rationale and goals of the projects, identifying domains for assessment, collecting data, making sense of the data and intervening were adapted to by facilitating online workshops, collecting data online and through proxy evaluators, while sharing methodological insights within the evaluation team. During evolving crises, like the COVID-19 pandemic, evaluators must embrace flexibility, leverage, and apply their knowledge of the evaluation context, lean on their strengths, purposefully reflect and share knowledge to optimise their DEs.